2014
DOI: 10.1016/j.yexcr.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Cell interactions and cell signaling during hematopoietic development

Abstract: Hematopoiesis is a key process that leads to the formation of all blood cell lineages from a specialized, multipotent cell, named the Hematopoietic Stem Cell (HSC). During development, the embryo produces several waves of hematopoiesis that produce specialized subsets of hematopoietic cells. Tissue interactions and cell signaling play an essential role in developmental hematopoiesis by allowing the formation of hematopoietic and endothelial cells (EC) from the mesoderm in particular in the yolk sac and by inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Our genetic analyses clearly demonstrate that attenuation of Dpp signaling affects HSCs maintenance in the early lymph gland. This reflects a great degree of similarity to the vertebrate AGM related HSCs that express BMP4 receptor and require BMP4 signaling as the niche signal from the neighboring mesenchyme for their maintenance (Durand et al, 2007; Drevon and Jaffredo, 2014). It has been demonstrated that both the vertebrate AGM and Drosophila cardiogenic mesoderm are specified by identical signals and house blood cell precursors originating from hemangioblasts (Mandal et al, 2004; Choi et al, 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Our genetic analyses clearly demonstrate that attenuation of Dpp signaling affects HSCs maintenance in the early lymph gland. This reflects a great degree of similarity to the vertebrate AGM related HSCs that express BMP4 receptor and require BMP4 signaling as the niche signal from the neighboring mesenchyme for their maintenance (Durand et al, 2007; Drevon and Jaffredo, 2014). It has been demonstrated that both the vertebrate AGM and Drosophila cardiogenic mesoderm are specified by identical signals and house blood cell precursors originating from hemangioblasts (Mandal et al, 2004; Choi et al, 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Signals from non-hematopoietic cell niches play an essential role in directing primitive hematopoiesis (Drevon and Jaffredo, 2014). In mouse and chick, hematopoietic mesoderm cannot autonomously differentiate as blood when cultured in isolation, but requires noncell-autonomous signals transmitted from visceral endoderm in order to do so (Belaoussoff et al, 1998;Wilt, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…During vertebrate hematopoiesis, stem cells differentiate along one of the various blood lineages (Drevon and Jaffredo, 2014). The first blood progenitors arise from mesodermal cells that are specified with a hematopoietic fate during gastrulation.…”
Section: Introductionmentioning
confidence: 99%